MEASUREMENT OF PAR AND ITS IMPACT ON CHRYSANTHEMUM (CHRYSANTHEMUM MORIFOLIUM RAMAT.) - SOUMITRA KOLEY,; MADHUMITA MITRA SARKAR, (The Bioscan, 2013)
An experiment was conducted at the Jaguli Instructional Farm, Faculty of Horticulture, Bidhan Chandra Krishi Viswavidyalaya, for two years (2009-10 and 2010-11) where three standard cultivars ( Snowball, Phil Houghton and SL- Ander Reffaud) of chrysanthemum were planted on 3rd August 2009 and 2010 in 1m2 plot laidout in the factorial randomized block design with three replication. Availability of photosynthetically active radiance (PAR) inside the polyshade, percentage of absorption, percentage of interception, albedo, percentage of interception, absorptance, transmittance and reflectance were computed. Absorption was found to be maximum when nitrogen (N2) was applied in two split irrespective of cultivar and date of observation. Among 3 cultivars, the Snowball (Cv1) recorded the highest absorption as well as absorptance. The lowest transmittance observed in case of N2 dose where as nitrogen application increased the reflectance.